Untersuchungen über Gallmücken. XIX. Gallmücken aus Blattgallen von Peucedanum oreoselinum (Diptera: Cecidomyiidae). - Stelter, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1975)
The species Jaapiella buhri spec. nov. and Macrolabis incognita spec. nov. are described form leaf galls of Peucedanum oreoselinum, and the characteristics differentiating them for closely related species are pointed out. Apparently the galls caused by these two species can not be distinguished. Nomenclatural Acts buhri Stelter, 1975 (Jaapiella), spec. n. incognita Stelter, 1975 (Macrolabis), spec. n.